Risks caused by the indiscriminate use of slimming drugs (Research, Society and Development, 2021)
Objective: To describe the risks and adverse effects caused by the indiscriminate use of slimming drugs used to treat overweight/obesity. Methods: This is a systematic review, based on studies on obesity and its treatment, focusing on the adverse factors described in these studies. This search was carried out on scientific bases such as SciELO, PubMed, Google Scholar, Bireme, CAPES Platform and Lilacs. Results: From the total of articles found (80,600 articles) which analyze different drugs used for the treatment of obesity, 14 were selected to compose this systematic literature review. Conclusion: there are cases in which drug treatment is necessary, and this being well oriented, prescribed and supervised, the benefits will be greater than the losses caused by the adverse effects. However, in reality, most of the times, this well-guided and prescribed treatment is a utopia, so these adverse effects take on greater proportions, outweighing the benefits.